Vetus Latina: Fragmente zum Alten Testament. Die Pelagianische Epistula ad quondam Matronam Christianam. Edited by Hermann Josef Frede with U. Fröhlich and H. Stanjele. (Vetus Latina: Aus der Geschichte der Lateinischen Bibel, 28.) Pp. 229. Freiburg: Herder, 1996. isbn 3 451 21937 9. Paper n.p - Horbury, William (The journal of theological studies, 2005)
This collection, introduced by the editor with the motto ‘Gather up the fragments that remain … ’, begins with two items from a palimpsest leaf discovered in the Ambrosian Library by Mirella Ferrari. This leaf forms part of a manuscript hitherto known from palimpsest fragments preserved in Vienna lat. 954; their original writing (5th–6th century) offered parts of the Old Latin Proverbs, classified at Beuron as the Old Latin MS. 165, and their eighth-century overwriting presented work ascribed by G. Morin to the early fifth century on the basis of style and content, and recognized by A. Dold as belonging to a single ascetical letter. The new leaf provides an addition (Prov.